Respuesta :

Answer:

[tex]\frac{ -b+/-\sqrt{b^2-4ac} }{2a}[/tex]

Step-by-step explanation:

1) the equation listed above is the quadratic formula! you can solve ANY quadratic equation with it

quadratic equations in the form of:

ax^2+bx+c

just substitute a,b,and c for the numbers in the quadratic equation!

2)factoring:

my 2nd favorite method:

your equation will be in the form of:

ax^2+bx+c

where you need to find:

what*what=c

and

what+what=b

once you find those two things out then substitute those numbers in place of "b"

for example:

x^2+7x+10

factors of 10:  5,2  10,1   -2,-5   -10,-1

factors of 10 that=7

5,2

so

x^2+5x+2x+10

now group this equation:

group a) x^2+5x

group b) 2x+10

gcf of group a)  x

so

x(x+5)

group b) gcf:2

so

2(x+5)

combine the numbers outside the parantheses:

(x+2)(x+5)=0

x+2=0

x=-2

x+5=0

x=-5

hence x=-2,-5

hope this helps!